The works of George Khirobosk in Byzantine and Old Slavic philological science - Звонська, Леся Леонідівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article considers the significance of George Khirobosk’s works in Byzantine and Old Slavic philological science; the sources and composition of «Izbornik of Svyatoslav 1073» are described; a comparative analysis of the names of the artistic means in the Greek text of George Khirobosk «Izbornik of Svyatoslav 1073» and his Old-Slavic translation «О образѣх»; the influence of the Greek treatise on the formation of the names of poetic tropes in the literary theory of Kievan Rus is studied. Byzantine literature, new in its tasks and content, which widely used the experience of ancient literature and culture, is mentioned in this article. In Byzantine science, the figure of Georgiy Khirobosk - a writer, riter, scholar - occupies a significant place. In the translation of the treatise of Hirobosk for the first time for the Southern and Eastern Slavs was revealed the content of a number of Greek rhetorical terms, a significant number of which later became entrenched with the names of Greek origin. The translation of the work of Georgiy Khirobosk, placed in "Izbornik", testifies to the high creative possibilities of the Old Slavonic language: in this first work on literary terminology in Kievan Rus, all the Greek names of poetic terms are transmitted by means of the Slavic language. At first glance, the system of poetic terms "Izbornik" appears archaic. However, modern literary science, along with Greek, uses translated terms. Also, the article deals with the aesthetic succession in the cultural development of the Greek people and the process of assimilating Christian literature methods and forms, symbols and artistic means.